The fishing cat: New insights on distribution in the northern sector of Chitwan National Park, Nepal - Maharjan, Rupesh; Mishra, Rama; Karki, Jhamak Bahadur (Nepalese Journal of Zoology, 2024)
Fishing cat Prionailurus viverrinus (Bennett, 1833) is an elusive and medium-sized feline species with distinguished marking patterns on their head and body separating them from other feline species. Despite being distributed widely among diverse geographic locations, their abundance has declined due to significant habitat loss and human disturbances. There exists a substantial research gap regarding their abundance and distribution in Nepal. In this article, we presented the updated documentation of the fishing cat distribution in the northern sector of Chitwan National Park through our species-focused camera trapping survey. The study was carried out between April and May 2021 with a total of 130 camera trap nights. We obtained images of fishing cats from three camera trap sites, less than one kilometer of aerial distance from the human settlements, indicating that the species could also be extensively using human-dominated landscapes within and around the parts of CNP. Our research also found that fishing cats are residing close to the Rapti riverbed where seasonal shallow water holes are more common, allowing them to hunt their prey easily.